Perjuangan Perempuan Menghadapi Kekuasaan Dalam Lakon Ã¢â‚¬Å“Susi DuyungÃ¢â‚¬Â: Ludruk Budhi Wijaya - Anwar, M. Shoim; Ambarwati, Listyo (LPPM Universitas PGRI Adi Buana Surabaya, 2017)
Ludruk Budi Wijaya Group is a cultural actor who is active in maintaining and developing the arts of thepeople. The characteristic of ludruk as a critical stage art is maintained, including the structure of the show. Ludruk isa channel for the aspirations of the little people and represents their lives. The